Battery Energy Storage Systems in Ships’ Hybrid/Electric Propulsion Systems - Marcin Kolodziejski; Iwona Michalska-Pozoga (Energies, 2023)
The shipping industry is going through a period of technology transition that aims to increase the use of carbon-neutral fuels. There is a significant trend of vessels being ordered with alternative fuel propulsion. Shipping’s future fuel market will be more diverse, reliant on multiple energy sources. One of very promising means to meet the decarbonisation requirements is to operate ships with sustainable electrical energy by integrating local renewables, shore connection systems and battery energy storage systems (BESS). With the increasing number of battery/hybrid propulsion vessels in operation and on order, this kind of vessel propulsion is becoming more common, especially in the segment of short range vessels. This paper presents review of recent studies of electrification or hybridisation, different aspects of using the marine BESS and classes of hybrid propulsion vessels. It also reviews several types of energy storage and battery management systems used for ships’ hybrid propulsion. The article describes different marine applications of BESS systems in relation to peak shaving, load levelling, spinning reserve and load response. The study also presents the very latest developments of hybrid/electric propulsion systems offered by leading maritime market manufacturers.